2020
DOI: 10.1080/17512786.2020.1805792
|View full text |Cite
|
Sign up to set email alerts
|

Activist-journalism and the Norm of Objectivity: Role Performance in the Reporting of the #MeToo Movement in Denmark and Sweden

Abstract: This article presents the results of a study examining the selfperceived roles of journalists covering the #MeToo movement in Denmark and Sweden. Drawing on qualitative interviews with journalists, editors and activists (N = 20) and participant observation at various #MeToo events, we examine the professional journalism cultures underpinning differences in the coverage and the broader public debate spurred by the movement in the two countries. The analysis is informed by the theoretical framework of role perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…With regard to Danish journalists, the subjects of this study, previous studies have shown that they strongly endorse the ideal of objectivity (Hartley & Askanius, 2020;Skovsgaard, 2010). In one study, 45 per cent of Danish journalists stated that it is "very important" to be as objective as possible (Skovsgaard et al, 2012).…”
Section: Theoretical Framework: the Many Faces Of Objectivitymentioning
confidence: 91%
“…With regard to Danish journalists, the subjects of this study, previous studies have shown that they strongly endorse the ideal of objectivity (Hartley & Askanius, 2020;Skovsgaard, 2010). In one study, 45 per cent of Danish journalists stated that it is "very important" to be as objective as possible (Skovsgaard et al, 2012).…”
Section: Theoretical Framework: the Many Faces Of Objectivitymentioning
confidence: 91%
“…The sectors could be connected to areas of interest ( n = 35), like sports, but many were profession based ( n = 43). There were, for example, groups from the university sector (Grubbström & Powell, 2020; Salmonsson, 2020), the media industry (Møller Hartley & Askanius, 2020; Sveningsson et al., 2022a), the music industry (Werner, 2022), the forest industry (M. Johansson et al., 2018), and the Church (Carstensen, 2022). A total of 78 groups were formed, gathering over hundred thousand participants who represented a broad group of women and non‐binaries, from teens to seniors, and from most parts of the country.…”
Section: #Metoo In Swedenmentioning
confidence: 99%
“…Those long-standing rules include objectivity and understanding news relevancy and avoiding conflicts of interest, whether personally or economically (“SPJ Code of Ethics,” 2014; Wasserman, 2010). More recently, normative theory has suggested that “objective” is too ambiguous of a term, and instead, journalists and journalism educators have heeded to using “seeking truth” as a journalistic standard (Baleria, 2020; Harlow & Brown, 2022; Hartley & Askanius, 2021; Raeijmaekers & Maeseele, 2017; Solkin, 2022; Wahl-Jorgensen, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%